A Novel Order Reduction Approach for LTI Systems Using Cuckoo Search Optimization and Stability Equation. Issue 2 (3rd March 2016) - Narwal, Amit; Prasad, B. Rajendra
ABSTRACT: A new reduction method is given which combines recently developed metahueristic cuckoo search optimization technique and stability equation method for obtaining reduced-order linear time invariant (LTI) system. This paper provides an efficient approach for reduction of both single-input single-output (SISO) and multiple-input multiple-output (MIMO) LTI systems. The lower order system obtained by the proposed technique retains the stability of higher order system and matches in steady-state value to the original model. The results of the proposed method are compared with other popular presented approaches of order reduction in the literature. The reduced systems obtained by the proposed method also have lower integral performance indices values than other order reduction techniques. The method is explained by numerical examples.